1995
DOI: 10.1111/j.1365-2494.1995.tb02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forage matting on rate of grass drying, rate of silage fermentation, silage intake and digestibility of silage by sheep

Abstract: The effects of forage maltifig on rate of grass drying and silage fermentation, digestibility, and intake were examined using perennial ryegrass swards. Treatments compared were: forage mats, where grass was processed through a laboratory scale macerator prior to matting and willing to 228 g dry matter (DM) kg"' (FM treatment); unconditioned grass which was direct ensiled at 163 g DM kg"' (DE treatment); unconditioned grass which was wilted for the same period as FM to 213 g DM kg"' (UC treatment); uncondition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Drying rates (day 1 only) for mower-conditioned (cond) and flail-mowed (flail) grass relative to unconditioned (uncond) grass at the same weight per unit area and initial dry-matter (DM) on rain-free days (n ϭ 20 for each treatment; mean of all post mowing treatments) 1·5 1·39 1·08 1·00 2·73 1·28 1·00 3·98 1·76 1·00 3 1·14 1·02 1·00 2·30 1·25 1·00 2·69 1·40 1·00 6 0·92 1·03 1·00 1·88 1·29 1·00 1·64 1·43 1·00 12 0·78 0·99 1·00 1·36 1·29 1·00 1·22 1·26 1·00 24 0·79 1·08 1·00 1·16 1·24 1·00 1·13 1·32 1·00 Mean 1·00 1·04 1·00 1·89 1·27 1·00 2·13 1·43 1·00 rate of grass drying. The use of wire-mesh trays is likely to overestimate moisture loss by between 8% and 23% (Frost et al, 1995). Despite this bias the results indicate that grass weight per unit area is a major factor affecting the rate of water loss from mown grass.…”
Section: Discussionmentioning
confidence: 84%
“…Drying rates (day 1 only) for mower-conditioned (cond) and flail-mowed (flail) grass relative to unconditioned (uncond) grass at the same weight per unit area and initial dry-matter (DM) on rain-free days (n ϭ 20 for each treatment; mean of all post mowing treatments) 1·5 1·39 1·08 1·00 2·73 1·28 1·00 3·98 1·76 1·00 3 1·14 1·02 1·00 2·30 1·25 1·00 2·69 1·40 1·00 6 0·92 1·03 1·00 1·88 1·29 1·00 1·64 1·43 1·00 12 0·78 0·99 1·00 1·36 1·29 1·00 1·22 1·26 1·00 24 0·79 1·08 1·00 1·16 1·24 1·00 1·13 1·32 1·00 Mean 1·00 1·04 1·00 1·89 1·27 1·00 2·13 1·43 1·00 rate of grass drying. The use of wire-mesh trays is likely to overestimate moisture loss by between 8% and 23% (Frost et al, 1995). Despite this bias the results indicate that grass weight per unit area is a major factor affecting the rate of water loss from mown grass.…”
Section: Discussionmentioning
confidence: 84%
“…Charmley et al (1997) found no effect on intake by sheep in metabolism cages. However, Frost et al (1995) found that intake of PC ryegrass silage by sheep was reduced by maceration. Mertens and Koegel (1992) showed that although maceration reduced silage intake, milk production was unaffected, suggesting better utilization of silage.…”
Section: Silage Qualitymentioning
confidence: 98%
“…Frost et al (1995) found that intake of ryegrass silage by sheep was reduced by maceration. However, Charmley et al (1997) found no effect on intake or digestibility of alfalfa silage by sheep.…”
Section: Restricting Fermentation Through Wiltingmentioning
confidence: 99%